Comparative safety of denosumab and romosozumab in osteoporosis: an analysis based on the FDA adverse event reporting system database - Sun, Jian; Lunzhu, Ciren; Wu, Yao; Li, Jun (Frontiers in Medicine, 2026)
ObjectiveDenosumab and romosozumab are two biological agents with potential immunomodulatory effects commonly used to treat osteoporosis. This study aimed to compare the safety of these two drugs using the FDA Adverse Event Reporting System (FAERS) with a focus on immune-related adverse reactions.MethodsData for the second quarter of 2019 (approval date for romosozumab) and the second quarter of 2025 were extracted from the FAERS database. After standardized data cleaning, disproportionality analysis and the Bayesian approach were applied to detect safety signals for the two biological agents simultaneously.ResultsAfter data extraction and cleaning, 38,784 and 10,007 reports were obtained for denosumab and romosozumab, respectively. Denosumab was associated with long-term cumulative risk and showed strong signals in musculoskeletal and metabolic disorders. In contrast, romosozumab demonstrated an acute and severe cardiovascular risk with strong signals for coronary artery disease and heart failure. Regarding immune-related events, denosumab was associated with osteoimmune complications such as noninfectious gingivitis, whereas the immune-related risk of romosozumab was limited to minor injection-site reactions.ConclusionResearch based on FAERS revealed distinct differences in the safety profiles of denosumab and romosozumab. Clinical decision makers should deepen their understanding of these features to advance personalized therapy and improve medication safety.